The Differences and Changes of Semi-Quantitative and Quantitative CT Features of Coronavirus Disease 2019 Pneumonia in Patients With or Without Smoking History - Xie, Xingzhi; Zhong, Zheng; Zhao, Wei; Wu, Shangjie; Liu, Jun (Frontiers in Medicine, 2021)
Objective To assess CT features of COVID-19 patients with different smoking status using quantitative and semi-quantitative technologies and to investigate changes of CT features in different disease state between the two groups. Methods 30 COVID-19 patients with current smoking status (29 men, 1 woman) admitted in our database were enrolled as smoking group and 56 COVID-19 patients without smoking history (24 men, 32 women) admitted during the same period were enrolled as a control group. 27 smoking cases and 55 control cases reached recovery standard and were discharged. Initial and follow-up CT during hospitalization and follow-up CT after discharged were acquired. 30 quantitative features including the ratio of infection volume and visual-assessed interstitial changes score including total score, score of ground glass opacity, consolidation, septal thickening, reticulation and honeycombing sign were analyzed. Results Initial CT images of smoking group showed higher scores of septal thickening（4.5 (0-5) VS 0 (0-4), p=0.001） and reticulation（0 (0-5.25) VS 0 (0-0) , p=0.001）as well as higher total score (7 (5-12.25) VS 6 (5-7) , p=0.008) with statistical significance than in the control group. The score of reticulation was higher in smoking group than in the control group when discharged (0.89 (0-0) VS 0.09 (0-0), p = 0.02). The score of septal thickening tended to be higher in smoking group than control group (4 (0-4) VS 0 (0-4), p = 0.007) after discharged. Quantitative CT features including infection ratio of whole lung and left lung as well as infection ratio within HU [-750, -300) and within HU [-300,49) were higher in control group of initial CT with statistical differences. The infection ratio of whole lung and left lung, infection ratio within HU (-, -750) and within HU [-750, -300) were higher in control group with statistical differences when discharged. This trend turned adverse after discharged and the values of quantitative features were generally higher in smoking group than in control group without statistically differences. Conclusions Patients with smoking history presented more severe interstitial manifestations and more residual lesion after discharged. More support should be given for COVID-19 patients with smoking history during hospitalization and after discharged.